Fundamentals of molecular evolution - Graur, Dan (Sinauer Associates, 2000)
This book describes the dynamics of evolutionary change at the molecular level, the driving forces behind the evolutionary process, the effects of the various molecular mechanisms on the structure of genes, proteins, and genomes, the methodology involved in dealing with molecular data from an evolutionary